The Role of Social Support to Foster Creative Thinking of Vocational Students In University: Mediating Effect of Creative Self-Efficacys - Ida Nugroho Saputro; Sukatiman Sukatiman; Abdul Haris Setiawan; Ayu Intan Sari (Qubahan Academic Journal)
Creative thinking skills have become one of the skills needed in the future. Many studies highlight the critical role of social support in forming students' creative thinking skills. However, the existing literature is still unclear about the structural mechanisms for building creative thinking with the role of supporting family, lecturers, and friends through students' creative self-efficacy. This study examines the effect of family support, lecturers, and friends on the ability to think through vocational students' creative self-efficacy mediators. There are 278 vocational students at the university involved in this study. Structural equation modelling is used to test direct and indirect effects. The study findings reveal that lecturer support and creative self-efficacy influence students' creative thinking. Meanwhile, the support of friends and family has no direct influence on creative thinking. Creative self-efficacy only significantly mediates the effect of lecturer support on creative thinking. The study results are discussed in depth by offering several important implications for vocational education practitioners both at universities and vocational high schools.